13C NMR Dataset Qualitative Analysis of Grecian Wines - Alberto Mannu; Ioannis K. Karabagias; Salvatore Baldino; Cristina Prandi; Vassilios K. Karabagias; Anastasia V. Badeka (Data, 2020)
The development of analytical techniques for characterizing food samples, especially for the wine industry, is a main topic of research. Regarding the classification of wines based on their geographical origin, nuclear magnetic resonance (NMR) spectroscopy represents a fast and effective tool for determining chemical fingerprints. Herein, a 13C NMR dataset, which was acquired for classification of Grecian wines through multivariate statistics, is reported and described. Thus, the main qualitative differences between grapes of the same geographical origin, observable by the visual analysis of the 13C NMR data, are discussed.